2020
DOI: 10.31557/apjcp.2020.21.2.349
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction in Carcinoma Cervix: Assessment in Post Treated Cases by LENTSOMA Scale

Abstract: Treatment for cervical cancer consists of hysterectomy, radiotherapy, chemotherapy and targeted therapy in different combination based on stage at presentation. However, late consequences of such radical treatments are known but not many Indian studies have reported it. Quality of life and impact on sexual health has become an important issue in view of long survival of cervical cancer patients. LENTSOMA scale is one such scale validated for scoring radiotherapy related morbidity. However, there is need for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 41 publications
0
17
0
3
Order By: Relevance
“…Um estudo prospectivo, conduzido por Shankar et al 28 , observou que a combinação da radioterapia com a cirurgia elevou a disfunção e insatisfação sexuais, principalmente em mulheres mais jovens. Notou-se que as queixas mais comuns, em ordem decrescente, foram a dispareunia, piora na qualidade da vida sexual e diminuição do interesse pelo sexo.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Um estudo prospectivo, conduzido por Shankar et al 28 , observou que a combinação da radioterapia com a cirurgia elevou a disfunção e insatisfação sexuais, principalmente em mulheres mais jovens. Notou-se que as queixas mais comuns, em ordem decrescente, foram a dispareunia, piora na qualidade da vida sexual e diminuição do interesse pelo sexo.…”
Section: Discussionunclassified
“…Notou-se que as queixas mais comuns, em ordem decrescente, foram a dispareunia, piora na qualidade da vida sexual e diminuição do interesse pelo sexo. Assim, o estudo observou que, no futuro, a ênfase sobre o dever de informar sobre o risco de alterações sexuais e gerais após a radioterapia deverá ser reforçada e há necessidade de que se construam escalas mais abrangentes abordando as perturbações físicas e psicológicas 28 .…”
Section: Discussionunclassified
“…This is confirmed by Shankar et al’s latest research. This study shows that a treatment consisting of surgery and radiotherapy in cervical cancer patients causes more sexual dysfunction and dissatisfaction [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pain experienced during sexual activity after treatment persisted as time progressed. 14 Another study in South Africa revealed that patients had poor sexual functioning and sexual satisfaction and the mean scores of 45.3% and 43.9% respectively as revealed by the Female Sexual Functioning Index tools that assessed their sexual functions. Additionally, women with menopausal status and sexual difficulties associated with the partner were significantly related to poorer sexual satisfaction.…”
Section: Methodsmentioning
confidence: 99%